2019
DOI: 10.1007/s11136-019-02236-3
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol, oxytocin, and quality of life in major depressive disorder

Abstract: Purpose Purpose: Quality of life (QoL) is greatly impaired in major depressive disorder (MDD). These impairments are not fully accounted for by symptom severity, may persist beyond depressive episodes, and are a risk factor for poor outcomes. MDD is often associated with prominent neuroendocrine changes and increased risk of chronic disease. However, there is a lack of research examining whether biological factors are related to QoL in MDD. This research examined relationships between cortisol, oxytocin, sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 53 publications
1
19
1
1
Order By: Relevance
“…Approximately 20% of all depressed patients develop a chronic course (Kessler et al, 2003). Untreated depression is associated with a decreased quality of life (Gao et al, 2019;Tang et al, 2019;Knight et al, 2020), increased suicide risk (four times more than the general population), and progressively worse health when associated with chronic physical illnesses, etc (Moussavi et al, 2007;Daly et al, 2010). Comorbidity with other chronic conditions (diabetes, hypertension, cardiovascular diseases, and cancer, among others) is high (Cassano and Fava, 2002;Katon, 2003;O'Neil et al, 2015;Read et al, 2017;Zhang et al, 2018) as is the case with other psychiatric diseases such as anxiety disorders (40 to 66%) (Aragonès et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 20% of all depressed patients develop a chronic course (Kessler et al, 2003). Untreated depression is associated with a decreased quality of life (Gao et al, 2019;Tang et al, 2019;Knight et al, 2020), increased suicide risk (four times more than the general population), and progressively worse health when associated with chronic physical illnesses, etc (Moussavi et al, 2007;Daly et al, 2010). Comorbidity with other chronic conditions (diabetes, hypertension, cardiovascular diseases, and cancer, among others) is high (Cassano and Fava, 2002;Katon, 2003;O'Neil et al, 2015;Read et al, 2017;Zhang et al, 2018) as is the case with other psychiatric diseases such as anxiety disorders (40 to 66%) (Aragonès et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The data were collected as part of a larger study of MDD, and the protocol as well as mean cortisol, oxytocin, and demographic data for this cohort have previously been reported in the context of help-seeking (37) and quality of life (38). This study was conducted in accordance with the recommendations of the Australian National Statement for the Ethical Conduct of Research.…”
Section: Participantsmentioning
confidence: 99%
“…If the most prevalent diagnoses of severe mental disorder in patients with dual disorders are considered, it is found that major depressive disorder (MDD) is one of the most frequently diagnosed conditions [ 19 , 20 , 21 , 22 ]. MDD is also associated with a worse quality of life [ 23 , 24 , 25 ]. MDD patients show worse HRQoL compared to the normal population, highlighting their low scores in the domains of social functioning [ 25 , 26 , 27 ], vitality, mental health, and emotional role [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%